Speak Acts of Commanding in a Collection of Short Stories by Annie M.G. Schmidt - Annisa Dhea Nurbaity (International Journal Labs, 2023)
The speech act commanding, which is part of the speech act directive, is one of the grammatical materials commonly taught in foreign language teaching to develop the form of scientific sentences. The research aims to look at command speech acts in a collection of short stories by Annie M.G. Schmidt's aim is for readers to understand and increase their knowledge about command speech acts in Dutch contained in short stories as we can produce examples of speech acts. This research uses qualitative enhancement with data collection techniques. This research uses listening and note-taking techniques by listening to the use of Dutch and noting the speech forms of the characters in the short story collection by Annie M.G. Schmidt. The results of the analysis show that the speech acts used in this research are illocutionary because the collection of short stories by Annie M.G. Schmidt contains various forms of speech acts such as assertive, directive, expressive, commissive, and declaration. Based on 5 types of short stories by Annie M.G. Schmidt, namely the short story De Reus en De Draak, the short story Het Meisje dat haar naam kwijt was, the short story De Kikvorst, the short story Het neurievolkje and the short story Het beest met achternaam, there are speech acts carried out directly or indirectly, but there are more direct speech acts than acts said indirectly.